Modern philosophical and legal principles of the classification of languages and language rights in foreign discourse: experience for Ukraine - Turyanytsya, V. V. (Науковий вісник Ужгородського національного університету. Серія Право, 2025)
The scholar analyzed the classification of languages by foreign scholars - philosophers, lawyers, linguists in the field of language rights - as a topical issue that often causes conflicts in society, the state and at the interstate level, and is also the cause of wars. The researcher of this problem emphasizes that language, language rights, their status and implementation have been and remain extremely relevant in our politically turbulent times with its unpredictable globalization processes and transformations in the coordinate system of national and international law based on the principles of democracy and the rule of law. The jurist notes that language is a delicate substance, the most delicate and painful problem of human existence. The status of language leads not only to linguistic, political, and legal conflicts, but also to civil and international wars. The full-scale war against Ukraine waged by the Russian Federation is a proof of this. The author emphasizes the need to apply international experience in solving this problem in multinational, post-totalitarian states on the basis of law, in particular, the classification of the status of languages and language rights arising from modern philosophical and legal principles in foreign discourse. Focusing on the classification, status of languages and, accordingly, language rights, the researcher concludes that it is necessary to realize and develop a new understanding of this phenomenon, the possibility of avoiding conflicts when reformatting the views of States in the interests of societies, States and interstate relations, taking into account the state and permanence of changes in the world, scientific and theoretical acquisition of conclusions and recommendations of philosophical and legal thought of our time, practical implementation at the level of national legislation, taking into account the basic international law. These are the theoretical, methodological and practical foundations of the need to address the universal human problem with a view to further avoiding conflicts and wars and a common awareness of the importance of this problem. Having analyzed this problem, outlined and characterized the positions of foreign scholars, the researcher draws conclusions regarding the practical use of experience and theoretical and methodological developments in Ukraine and post-Soviet countries which have embarked on the path of democracy and legal development.